La última acuñación de Fernando VII (1833). Imagen documental de una nueva realidad política - De Francisco Olmos, José María (Revista General de Información y Documentación, 2007)
This item shows the documentary use of the coin as a means of propaganda used by the last government of Ferdinand VII (1833), who, in the middle of a dynastic and political crisis close to the civil war, ordered a change in the types and legends of his main coin, the silver “duro”, in order to make it more adequate to the new political situation that would take place after the king’s death, i.e., the crowning of his daughter and the entrance of new liberal ministers in the government, that were meant to reinforce the starting Spanish constitutionalism.